Evaluasi Sales Performance PT. Lion Superindo Pekalongan - Purwanto, Teguh; Fatah, Khoirul; Majid, Musfirah (Neraca, 2024)
This research aims to evaluate sales performance at PT. Lion Super Indo using the least squares method. The data used in this research includes monthly sales reports for 2022. Data analysis was carried out by applying the least squares model to estimate PT's sales performance. Lion Supeindo. The research results show that there is a significant positive correlation between promotional activities and increased sales. In addition, the least squares model developed succeeded in providing accurate predictions regarding the impact of promotions on future sales. This research provides a practical contribution to the management of PT. Lion Superindo Pekalongan in planning and optimizing sales promotion strategies. By utilizing the forecasting model that has been developed, companies can make more informed decisions regarding the allocation of promotional budgets and the optimal timing of promotional campaigns. REFERENSI Anderson, D. R., Sweeney, D. J., & Williams, T. A. (2011). Essentials of Modern Business Statistics with Microsoft Excel. South-Western Cengage Learning. Badmus,M.A dan Ariyo.O.S. 2011. Forecasting cultivated areas and production of Maize in Nigerian using ARIMA Model. Asian journal of agricultural science. 3(3):171-176 Churchill, G. A., & Peter, J. P. (1998). Marketing: Creating Value for Customers. Irwin/McGraw-Hill. Djarwanto.subagyo pangestu:2000.Statistik induktif.BPFE Yogyakarta Gujarati, D. N., & Porter, D. C. (2009). Basic Econometrics (5th ed.). McGraw-Hill/Irwin. Gujarati, D. N., & Porter, D. C. (2009). Basic Econometrics. McGraw-Hill. Hariri F R, 2016. Metode least square untuk memprediksi penjualan sari kedelai rosi. Jurnal simetris volume 7 no 2 Hyndman, R. J., & Athanasopoulos, G. (2018). Forecasting: Principles and Practice (2nd ed.). OTexts. Kotler, P., & Keller, K. L. (2016). Marketing Management. Pearson Education. Kutner, M. H., Nachtsheim, C. J., Neter, J., & Li, W. (2004). Applied Linear Statistical Models. McGraw-Hill. Linda, Puspa., Marihat Situmorang., Gim Taringan, “Peramalan Penjualan Produksi Teh Botol Sosro pada PT. Sinar Sosro Sumatera Bagian Utara Tahun 2014 dengan Metode Arima Box Jenkins”, Saintia Matematika, vol 02, no. 03 pp. 253-266, 2014 Makridakis, S., Wheelwright, S. C., & Hyndman, R. J. (1998). Forecasting: Methods and Applications (3rd ed.). John Wiley & Sons. Montgomery, D. C., Jennings, C. L., & Kulahci, M. (2015). Introduction to Time Series Analysis and Forecasting. John Wiley & Sons. Montgomery, D. C., Peck, E. A., & Vining, G. G. (2012). Introduction to Linear Regression Analysis. Wiley. Paramita, Citra., Dul Muid, “Analisa Perbandingan Metode Peramalan Penjualan Bahan Bakar Minyak dengan Standar Kesalahan Peramalan (SKP) pada PT. Pertmina (Persero) Region IV Jateng dan DIY”, 2011. Putra Pamungkas, Danar. 2016.implementasi metode least square untuk prediksi penjualan tahu pong.jurnal ilmiah nero Volume2 Nomer 2 Raju, T. S., & Konda, K. (2017). Sales Performance Analysis Using Regression. Journal of Business and Management, 19(2), 1-7. Rizaldi, H. (2022). The influence of brand popularity, perceived quality, price, and need on purchase intention iPhone products in Purwokerto. Jurnal Akuntansi, Manajemen dan Ekonomi, 24(2), 14-22. Sadli,Muhammad.2017.Implementasi sistem cerdas Least square dalam meramalkan pemenuhan kebutuhan stock listrik dikota lhokseumawe.jurnal ecotipe. Volume 14 no.2 Solikhah, F., Purwanto, T., Arifiyanto, M., Rizaldi, H., & Moegiri, M. (2023). ANALISIS PENGARUH RELIGIUSITAS, TINGKAT PENDAPATAN, KUALITAS PELAYANAN DAN TINGKAT KEPERCAYAAN TERHADAP MINAT MEMBAYAR ZAKAT (Studi Kasus pada Lazismu Kota Pekalongan). Neraca, 19(2), 76-86. Sudarismiaty A., dan Tri Diah Sari M., 2016. Analisis Peramalan Penjualan untuk menentukan rencana produksi pada UD Rifa’i. Jurnal Ekonomi dan Bisnis GROWTH. Vol 14 No 2. Sugiyono., 2017. Metode Penelitian kuantitatif,kuantittif dan R&D Bandung. CV Alfabet Sun, W., & Zhou, H. (2014). Prediction of Sales Using Least Squares Method. International Journal of Business and Social Science, 5(6), 180-184. Wilda Nur Octavia,R., dan Chotijah.,U.2022. Implementasi Metode Least Square untuk memprediksi penjualan kue donat dan Bomboloni. Jurnal Ilmiah Tekhnik Informatika dan Sistem Informasi. Vol 11 No 1